2019
DOI: 10.30997/jn.v4i2.1552
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Financial Technology Towards the Advancement of Islamic Banking in Indonesia

Abstract: Responding to the digital economy in the era of industrial revolution 4.0, the quality of sharia banking services in Indonesia is estimated and expected to increase significantly, in order to reach all levels of society, especially for people who live in the 3T area (terdepan/frontier, terluar/outermost, and terpencil/isolated). However, currently the quality of sharia banking services in Indonesia is not yet satisfactory, especially by people living in the 3T area. this research, trying to answer the challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Furthermore, mobile banking offers secure and convenient access to banking products and channels (Laukkanen, 2007) and allows customers to monitor their own financial assets. Another study found that mobile banking users feel assured because mobile banking is equipped with two security systems, namely, password protection and immediate account blocking in the event of the theft or loss of a mobile phone (Darussalam et al , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, mobile banking offers secure and convenient access to banking products and channels (Laukkanen, 2007) and allows customers to monitor their own financial assets. Another study found that mobile banking users feel assured because mobile banking is equipped with two security systems, namely, password protection and immediate account blocking in the event of the theft or loss of a mobile phone (Darussalam et al , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These findings provide important insights into the context of the banking industry, especially in facing the challenges of the pandemic. BPR and BPRS can take advantage of technological changes and digitalization to improve their performance and meet customer needs efficiently (Abbas et al, 2015;Darussalam et al, 2019;Safiullah, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Penelitian analisis SWOT mengenai Fintech pada dunia perbankan di Indonesia (Basuki & Husein, 2018;Chrismastianto, 2017;Marginingsih, 2019;Muchlis, 2018). Penelitian Fintech dikaitkan dengan perbankan islam atau syariah (Darussalam, Tutuko, Dahlan, Hudaifah, & Tajang, 2018;Nurul & Ningrat, 2018). (Tripalupi, 2019).…”
Section: Pendahuluanunclassified